2019
DOI: 10.1103/physrevb.99.184501
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the proximity effect in two-dimensional unconventional superconductors with Rashba spin-orbit interaction

Abstract: We study the anomalous proximity effect in diffusive normal metal (DN)/unconventional superconductor junctions, where the local density of states (LDOS) in the DN has a zero-energy peak due to the penetration of the odd-frequency spin-triplet s-wave pairing. In this study, we consider a two-dimensional unconventional superconductor on the substrate in the presence of a Rashba spinorbit coupling (RSOC) λ, where the Rashba vector is parallel to the z-direction. The anomalous proximity effect, originally predicte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 120 publications
2
10
0
Order By: Relevance
“…It is known that SOC induced pairing does not break the time reversal symmetry 23 , and the presence of the SOC also leads to mixing of the triplet and the singlet components. In the context of noncentrosymmetric superconductors, the tunneling conductance for SN junctions has been studied in systems with SOC [24][25][26][27][28] . However, the effect of the SOC and the conductance for a mixed parity supercon- ductor in a T-junction device is not known.…”
Section: Introduction-mentioning
confidence: 99%
“…It is known that SOC induced pairing does not break the time reversal symmetry 23 , and the presence of the SOC also leads to mixing of the triplet and the singlet components. In the context of noncentrosymmetric superconductors, the tunneling conductance for SN junctions has been studied in systems with SOC [24][25][26][27][28] . However, the effect of the SOC and the conductance for a mixed parity supercon- ductor in a T-junction device is not known.…”
Section: Introduction-mentioning
confidence: 99%
“…Odd-frequency (odd-ω) pairing can emerge as a bulk or induced phenomena and it has been shown that the main ingredient in both cases relies on breaking the system symmetries [2][3][4][5]. For instance, it has been shown that odd-ω correlations can be induced in normal-superconductor junctions [3,[5][6][7][8][9][10][11][12][13][14], where their emergence occurs because the spatial parity of Cooper pairs is broken at the junction interface. Moreover, under the presence of a spin field in such junctions, e.g., from a magnetic field or spin-orbit coupling, spins get mixed, which then gives rise to even more exotic spin-triplet odd-ω correlations [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Odd-frequency (odd-ω) pairing can emerge as a bulk or induced phenomena and it has been shown that the main ingredient in both cases relies on breaking the system symmetries. [2][3][4][5] For instance, it has been shown that odd-ω correlations can be induced in normal-superconductor junctions, 3,[5][6][7][8][9][10][11][12][13][14] where their emergence occurs because the spatial parity of Cooper pairs is broken at the junction interface. Moreover, under the presence of a spin field in such junctions, e.g.…”
Section: Introductionmentioning
confidence: 99%